2014
DOI: 10.1073/pnas.1410372111
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of Drosophila melanogaster repeatomes in response to a sharp microclimate contrast in Evolution Canyon, Israel

Abstract: Repeat sequences, especially mobile elements, make up large portions of most eukaryotic genomes and provide enormous, albeit commonly underappreciated, evolutionary potential. We analyzed repeatomes of Drosophila melanogaster that have been diverging in response to a microclimate contrast in Evolution Canyon (Mount Carmel, Israel), a natural evolutionary laboratory with two abutting slopes at an average distance of only 200 m, which pose a constant ecological challenge to their local biotas. Flies inhabiting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 58 publications
1
50
0
Order By: Relevance
“…Barbara McClintock [1984] formerly suggested that the activity of mobile elements in the genome represented a reaction to environmental stressors. This hypothesis was supported by several other authors [Capy et al, 2000;Kidwell, 2002;Chénais et al, 2012;Piacentini et al, 2014], and numerous cases of transposon activation due to environmental stress conditions have been observed in plants, where one of the most influential environmental factors is represented by temperature [Vitte and Panaud, 2005;Kelly and Leitch, 2011;Chénais et al, 2012;Ito, 2013;Wheeler, 2013;Ishiguru et al, 2014;Kim et al, 2014]. Examples of correlations between environmental stressors and transposon activity are rarer in the animal kingdom.…”
Section: Mechanisms and Causesmentioning
confidence: 56%
See 1 more Smart Citation
“…Barbara McClintock [1984] formerly suggested that the activity of mobile elements in the genome represented a reaction to environmental stressors. This hypothesis was supported by several other authors [Capy et al, 2000;Kidwell, 2002;Chénais et al, 2012;Piacentini et al, 2014], and numerous cases of transposon activation due to environmental stress conditions have been observed in plants, where one of the most influential environmental factors is represented by temperature [Vitte and Panaud, 2005;Kelly and Leitch, 2011;Chénais et al, 2012;Ito, 2013;Wheeler, 2013;Ishiguru et al, 2014;Kim et al, 2014]. Examples of correlations between environmental stressors and transposon activity are rarer in the animal kingdom.…”
Section: Mechanisms and Causesmentioning
confidence: 56%
“…Examples of correlations between environmental stressors and transposon activity are rarer in the animal kingdom. However, similar connections were noted in Drosophila melanogaster , where differences in the rate of transposition were related to the development of temperature [Capy et al, 2000;Kim et al, 2014;Piacentini et al, 2014] and to the development of a resistance to pesticides [Chénais et al, 2012]. In human cells a reorganization of the transcriptome after thermal shock was described, putatively involving SINE transposon sequences [Wheeler, 2013].…”
Section: Mechanisms and Causesmentioning
confidence: 65%
“…10; see also refs. [13][14][15][16]. The first analysis of incipient SS of spiny mice, A. cahirinus (16), was based on mtDNA and AFLP.…”
Section: Resultsmentioning
confidence: 99%
“…These organisms include Bacillus simplex (11), wild barley [Hordeum spontaneum (10,12)], fruit flies [Drosophila melanogaster (13,14)], beetles [Oryzaephilus surinamemsis (15)], and spiny mice [Acomys cahirinus (16)]. All five model organisms display evolution in action of microclimatic adaptation and incipient sympatric adaptive ecological speciation on the tropical and temperate abutting slopes of EC I that are, on average, 250 m apart (10).…”
mentioning
confidence: 99%
“…Other fascinating recent studies, bolstered by the recent advances in DNA sequencing technologies, have exemplified the role of TE insertions as a functional source of genetic evolution in insects. At the environmental level, divergent TE contents have been correlated with climate adaptation in specific strains [72,73 ]. Two additional studies also report that TEs generate somatic mutations in the drosophila brain during development [74 ] and aging [75 ] suggesting that TE activity may contribute to the establishment of neuronal mosaïcism as well as to agedependent loss of neuronal function.…”
Section: Impact Of Tes On Genome Adaptationmentioning
confidence: 99%